Kinetics and mechanism of oxidation of GSH by cis-(diaqua)-bis-(ethylenediamine) Cobalt(III) ion - Mohanty, Bijaylaxmi; Behera, Jashoda; Acharya, Sridhara; Mohanty, Prakash; Patnaik, Ajay Kumar (International Journal of Advanced Chemistry, 2014)
The kinetics of GSH oxidation to GSSG by cis-(diaqua)-bis-(ethylenediamine) cobalt(III) perchlorate was studied spectophotometrically under pseudo-first order condition using 103[Co(III)] = 5 mol dm-3, 2.5 ? 102[GSH] ? 10.00 mol dm-3, 3.5 ? pH ? 5.0, 318K ? T ? 333K at a fixed ionic strength I = 0.3 mol  dm-3 (NaClO4). The disappearance of [Co (III)] at 500 nm with time showed first-order kinetic trend. The first order dependence on [GSH] and pH was observed. Temperature dependence of the second order rate constant k'2 = kobs/[GSH] were analysed for the Co(III)-OH23+ (k1) and Co(III)-OH2+ (k2) reactivities. An outer-sphere complex formation between the Co(III) and GSH followed by one-electron transfer from GSH to Co(III) resulting the formation of Co(II) and GSx radical. The GSx radical undergoes fast dimerisation to GSSG. Activation parameters were calculated. These values favor the electron transfer reaction.   Keywords: Co (III) complex, GSH, GSSG, Spectrophotometer, Redox reaction.